2005
DOI: 10.1016/j.otohns.2004.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the diagnosis and treatment of primary hyperparathyroidism from 1995 to 2003

Abstract: These results support a greater role for the treatment of primary hyperparathyroidism using less invasive approaches. EMB rating: B-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
432
2
42

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 695 publications
(490 citation statements)
references
References 194 publications
14
432
2
42
Order By: Relevance
“…Ultrasonography is an efficient, non-invasive imaging modality with a sensitivity of 79% in locating adenomatous glands. 7 Parathyroid scintigraphy has been shown in the same meta-analysis to have a sensitivity of 88% and it is widely acknowledged that the two modalities, in experienced hands, offer optimum location in single gland disease. MB can be considered an adjunct to these measures by complementing and confirming the findings but also offering an important intraoperative marker in multiglandular or ectopic disease, where sensitivity rates are far lower.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography is an efficient, non-invasive imaging modality with a sensitivity of 79% in locating adenomatous glands. 7 Parathyroid scintigraphy has been shown in the same meta-analysis to have a sensitivity of 88% and it is widely acknowledged that the two modalities, in experienced hands, offer optimum location in single gland disease. MB can be considered an adjunct to these measures by complementing and confirming the findings but also offering an important intraoperative marker in multiglandular or ectopic disease, where sensitivity rates are far lower.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of different imaging methods have demonstrated the superiority of parathyroid scintigraphy for preoperative localization [26]. One systematic review of the medical literature showed that the overall sensitivity of dual-phase 99m Tc sestamibi scintigraphy in comparison with high-resolution Ultrasonography (US) was 88% versus 78% for single adenomas, 30% versus 16% for double adenomas, and 44% versus 35% for multiplegland hyperplasia [27].…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive techniques have been widely adopted due to the recognition that the majority of patients with hyperparathyroidism have single gland disease [5]. If the single hyperfunctioning gland can be removed in a less invasive fashion, and cure assured, then the older standard of four-gland exploration under general anesthesia with a generous incision is unnecessary.…”
mentioning
confidence: 99%
“…It is impossible to determine in the literature whether the use of the intraoperative nuclear medicine probe makes a difference in outcome [12]. As the vast majority of endocrine surgeons do not utilize the probe and have equivalent outcomes to those surgeons who do [5], it seems to be an unnecessary adjunct.…”
mentioning
confidence: 99%
See 1 more Smart Citation